The Influence Of Parenting Education On The Growth Of Children In Pengadan Village - Marhawa Marhawa; Andi Lis A.G; Nino Adib Chifdillah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Growth is a change in the size and increase in the number of cells, tissues and body structures that are quantitative so that they can be measured in units of length or weight. In addition to good and sufficient nutrition, another important factor that will help children to grow healthy and be able to achieve their optimal abilities is proper parenting. The purpose of this study was to determine the effect of parenting education on children's growth in Pengadan Village. This research method is a quantitative research with a pre-experiment design (one-group pretest-posttest design). The population in this study were all parents and children aged 1 month – 2 years in Pengadan Village. The sampling technique used in this study was non-probability sampling of the accidental sampling type with a total of 20 respondents. Data were analyzed using the Wilcoxon test. The results showed that children's growth based on weight, height and head circumference had increased after being given the intervention. The results of bivariate analysis showed that there was an influence between parenting education on children's weight (0.011), children's height (0.027) and children's head circumference with (0.002) with an alpha value of 0.05. There is an increase in growth after the intervention is carried out and there is an effect of parenting education on the growth of children in Pengadan Village.